CFD Analysis of Diverse Serrated Blade Configuration Effects on Fluid Flow of a Modified Centrifugal Fan - Zaimar Zaimar (President University, 2021)
This paper presents the effects of the diverse serrated blade configurations on airflow characteristics of a modified centrifugal fan by CFD. This application is investigated to improve aerodynamic performance. These configurations (USB, ISB, USB, OSB) are simulated at the impeller speed levels by CFD. Then tested to analyze airflow characteristic values by ANCOVA test. The simulation results show that the BSB configuration achieves the high static pressures about 84.5-214.7 Pa in the wall zone. While the ISB generates the lower TKE in all the zones, except in the impeller zone. It produces about 0.51-12.47 m2s-2 TKE in the wall zone. The ANCOVA test results indicate that the effects of the impeller speed are very significant (a < 0.01) on the airflow characteristics in all the zones, except for static pressure is no significant (a > 0.05) in the impeller and fluid flow zone. The effect of the serrated blade configurations is very significant on static pressure in the inlet and wall zone, and significant (a < 0.05) in the fluid flow zone. While it is very significant to air velocity in the impeller, fluid flow, and wall zone, and very significant on TKE in the impeller zone and outlet zone.